Company size, work-home interference, and well-being of self-employed entrepreneurs - Isabelle Godin; Pierre Desmarez; Céline Mahieu (BMC, 2017)
Abstract Background The impact of working conditions on the health and well-being of workers of large enterprises has been widely described. This influence has not been studied as extensively in very small and medium-sized enterprises mainly due to methodological difficulties. Smaller organisations nevertheless constitute a reality that needs to be better understood. Methodology The aim of this article is to better understand the working conditions of entrepreneurs in small and medium-sized enterprises, to describe the impact of these conditions on their health and well-being, and to learn how their work affects their private lives. This is why a study was conducted in 2015-2016 on a selected sample of entrepreneurs in the Brussels-Capital Region (n = 140). The survey form included questions pertaining to the work environment, motivations underlying the choice of activities, robustness of the business, work-home interference, work-related stress, work satisfaction, self-reported health indicators, and socio-demographic status. The results were compared with those from another survey on workers in small shops conducted between 2012 and 2015 within the same Region (n = 104). Results The number of entrepreneurs who participated in the survey added up to 140, with an even distribution between men and women. Two results are highlighted. The first concerns the difficulties faced by entrepreneurs working with a small team (1 to 4 employees): they are more stressed, report having heavy workloads, describe their health more negatively, consume more sedatives, and claim to suffer from loneliness more often than those working with larger teams or alone. Comparatively, in the study on shopkeepers, business owners working alone found themselves in a worse situation regarding their health and well-being. The second finding involves the difficulties entrepreneurs face when it comes to combining work and family life, and for which gender inequalities were noted. This phenomenon remains insufficiently explored amongst small business owners. Conclusion In spite of the difficulties encountered at work, commitment to their chosen profession remains strong amongst entrepreneurs. Our results enable us underscore the aspects of entrepreneurial activity that should be taken into account whilst setting up support mechanisms or promoting entrepreneurship, especially amongst and for women.